The future of work in the smart city: Managing virtual work by leveraging smart cities to achieve organizational strategy - Joshua Olusegun FAYOMI; Zainab Abdulqadir SANI (Smart Cities and Regional Development Journal)
The goal of the organization is to maintain and increase productivity of its resources including human capital. A clear assessment of all the available resources to management provides requisite information to enable them to allocate work tasks and monitor and assess outputs. The way work is done is changing across most industries and the future of work is one that has been celebrated and researched by experts and scholars alike. The ongoing COVID-19 pandemic has opened up the virtual work sphere as a paradigm for all organizations to explore, and many otherwise traditional work arrangements are beginning to innovate around how their work functions are achieved. This paper explores the concepts of smart cities, the future of work and virtual work. And through a mixed method of interviews and surveys identifies how organizations are leveraging on the advantages of smart cities in planning and implementing work arrangements for their employees in order to cope with the current pandemic and what their strategy would be overall when the situation comes back to normal. About 8 top managers were interviewed and 59 employees currently working virtually were surveyed. Responses were analysed and connectivity, flexibility and autonomy were identified as factors organizations considered as they planned and implemented virtual work arrangements. And their outlook for the future certainly included virtual work arrangement for at least a fraction of their employees as working from home, cafes, hotels etc has become a norm today and is generally accepted as a legitimate work arrangement between organizations and their employees.